Assessment of Knowledge Regarding Antibiotic Use, its Resistance, and Future Consequences among Higher Secondary Students in Private Schools of Kathmandu Valley: Assessment of Knowledge Regarding Antibiotic Use, its Resistance, and Future Consequences among Higher Secondary Students in Private Schools of Kathmandu Valley - Deo, Dr. Satish Kumar (International Journal of Pharmaceutical & Biological Archive, 2020)
Antimicrobial resistance poses a growing threat to public health, as infections from resistant strains of microbial become increasingly difficult and expensive to treat, resulting in prolonged illness and greater risk of death. A cross-sectional descriptive study was done among 471 higher secondary level students of private schools in Kathmandu Valley. Data were collected from Grade 11 and 12 non-science faculty students through self-administered questionnaires. Half (50.5%) of the students gave correct response by saying that antibiotic kills bacteria and 49.1% said that it is for fever. Majority (93.0%) of them said that it should be taken with water. Regarding the response on when to stop taking antibiotic, 46.9% said correctly by saying when all prescribed medicines are taken whereas and 40.8% said that after feeling better. More than half (58.8%) of the students had not heard about antibiotic resistance, whereas those who have heard among them 24% of students said that they had heard from doctor and nurses and 21.8% from family member and friends. Nearly one-third (32.7%) of students knew that antibiotic resistance occurs using antibiotic when they are not necessary. Regarding the response on consequences of antibiotic resistance, more than one-third (38.2%) of students gave correct answer. Nearly half of the students have lack of knowledge about antibiotic. Thus, it is imperative to create awareness among students by introducing a specific course on antibiotic in the 9th and 10th grade core curriculum to prevent antibiotic resistance and its consequences.